The Italian Social Protection System : The Poverty of Welfare - Rostagno, Massimo; Utili, Francesca (Washington, D.C. : International Monetary Fund, 1998)
Italy's system of social protection has come under criticism for being fragmented and excessively skewed toward pensioners and 'insiders.' After setting up a consolidated presentation of the social security accounts, this paper provides an empirical assessment of the effectiveness of the welfare system, relying on a survey of households' incomes and wealth. It concludes that, owing to ill-designed targeting mechanisms, less than a quarter of total spending on the welfare instruments under review accrues to families whose own resources fall short of the poverty line. The paper then proposes a new means-testing formula.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet